2017
DOI: 10.1002/lol2.10043
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus availability regulates intracellular nucleotides in marine eukaryotic phytoplankton

Abstract: Marine eukaryotic phytoplankton adapt to low phosphorus (P) in the oceans through a variety of step-wise mechanisms including lipid substitution and decreased nucleic acid content. Here, we examined the impact of low P concentrations on intracellular metabolites whose abundances can be quickly adjusted by cellular regulation within laboratory cultures of three model phytoplankton and in field samples from the Atlantic and Pacific Oceans. We quantified the relative abundances of monophosphate nucleotides and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…Compared to S1 and S2, there were increases in the relative expression of lipid processing, and purine metabolism in S3. It has recently been shown that A. anophagefferens , and other eukaryotic phytoplankton, modulate intracellular metabolites related to purine metabolism when P-deficient (Kujawinski et al, 2017). Eukaryotic phytoplankton are also well known to remodel their membrane lipids in response to P deficiency (Van Mooy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to S1 and S2, there were increases in the relative expression of lipid processing, and purine metabolism in S3. It has recently been shown that A. anophagefferens , and other eukaryotic phytoplankton, modulate intracellular metabolites related to purine metabolism when P-deficient (Kujawinski et al, 2017). Eukaryotic phytoplankton are also well known to remodel their membrane lipids in response to P deficiency (Van Mooy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules have been identified in culture experiments and/or detected in field samples to highlight some of the important microbial interactions in the surface ocean (Amin et al, 2015;Johnson et al, 2016;Repeta et al, 2016;Heal et al, 2017;Kujawinski et al, 2017). Targeted metabolomic studies focus on individual, well-characterized substrates whose concentrations and cycling can be followed precisely in incubations and in field settings.…”
Section: Introductionmentioning
confidence: 99%
“…This approach paired with high acquisitions speed (>1 Hz) of state of the art instruments results in thousands of spectra per LC-MS/MS run. For a reliable data analysis and reproducible interpretation of the results, bioinformatic workflows including comprehensive databases and statistical significance estimation are crucial (da Silva et al, 2015;Böcker, 2017;Scheubert et al, 2017;Weber et al, 2017) and have been very recently employed for marine metabolomic studies Hartmann et al, 2017;Kujawinski et al, 2017;Longnecker and Kujawinski, 2017). With these new bioinformatic tools and instrumental improvements in sensitivity, acquisition speed and resolution we anticipate that the techniques used for DOM characterization will further shift toward non-targeted analyses using high-resolution LC-MS/MS that provide inventories of molecular structures in complex environmental datasets.…”
Section: Introductionmentioning
confidence: 99%
“…LC MS/MS analysis of organic matter composition using orbital ion‐trap and quadrupole time of flight MS has been employed to identify potential structure and chemical formula of organic compounds through comparison to library mass spectra, mainly in marine systems (Kujawinski et al, ; Longnecker & Kujawinski, ). These instrumentations have lower resolving power compared to the FTICRMS and are characterized by significantly higher scan speeds due to the coupling with liquid chromatography.…”
Section: Introductionmentioning
confidence: 99%